Jianwei Xiaoshi oral liquid attenuates high-calorie diet-induced dyspepsia in immature rats via regulating the pancreatic secretion pathway and maintaining the homeostasis of intestinal microbiota - Yan Zhang; Xiaolu Wei; Shan Jiang; Wenya Gao; Kun Wang; Hongjie Wang; Huijun Wang; Nan Si; Yanyan Zhou; Keke Luo; Mengxiao Wang; Yuyang Liu; et al. (Chinese Medicine)
Abstract Background Jianwei Xiaoshi oral liquid (JWXS), a classical traditional prescription comprising various edible medicinal plants, has demonstrated significant efficacy in treating paediatric indigestion. It originates from Jianpi Pill, which is developed in the Ming Dynasty and nourishes the spleen and regulates gastrointestinal function. However, the specific molecular mechanisms involved remain unclear. Methods To elucidate the material base of JWXS and its underlying mechanism in treating dyspepsia, the UHPLC–Q–Orbitrap HRMS method and network pharmacology were utilized. This was followed by pharmacological experiments, transcriptomics analyses and gut microbiota studies to further investigate the effects of JWXS on dyspepsia. Results A total of 105 compounds, mainly flavonoids, alkaloids, organic acids and cyclic peptides, were identified. According to the five principles of generic drug properties, 43 candidate compounds were screened out. Their efficacy was verified through gastric emptying and intestinal propulsion experiments. Transcriptomic analysis revealed that JWXS primarily alleviated dyspepsia symptoms by regulating the secretion of 8 key proteins in the pancreatic secretion pathway. The differences in the gut microbiota, as identified through 16S rRNA and ITS2 sequencing, were subsequently more pronounced than those observed in the bacterial microbiota of the model group. In total, 15 differential bacteria and 16 differential fungi were identified. Targeted metabolomics analysis of SCFAs revealed a significant decrease in valeric acid (VA), acetic acid (AA), and isovaleric acid (IVA) levels in the model group, which were restored to the corresponding levels after the administration of JWXS. Correlation analysis revealed that VA, AA, and IVA were positively correlated with Lactobacillus and Bacteroides, and negatively correlated with Aspergillus and Candida. This further suggested that JWXS might alleviate symptoms of indigestion by regulating the composition of the microbiota, increasing the variety and quantity of beneficial bacteria, reducing fungal contamination, and further increasing the levels of SCFAs in the body. Conclusion JWXS improved functional dyspepsia in immature rats via a mechanism involving the regulation of the secretion of 8 key proteins in the pancreatic secretion pathway and the amelioration of flora disorders. Graphical Abstract